Effect of Motivation and Work Environment on Employee Performance in Work Unit Implementation on the Jakarta Metropolitan I National Road - Pratama, Guruh Dwi (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
The purpose of this study was to determine motivation and work environment for employee performance in Work Unit Implementation on the Jakarta Metropolitan I National Road. The method used is descriptive method with an associative approach. The sampling technique used was proportional random sampling with a sample of 60 respondents. The analysis tool uses validity test, reliability test, classic assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this study are that motivation has a positive and significant effect on employee performance by 43.1%. Hypothesis testing is obtained tcount> ttable or (6.628> 2.002), so that H0 is rejected and H1 is accepted, meaning that there is a positive and significant influence between motivation on employee performance in Work Unit Implementation on the Jakarta Metropolitan I National Road. The work environment has a positive and significant effect on employee performance by 40.7%. Hypothesis testing is obtained tcount> t table or (6.311> 2.002) so that H0 is rejected and H2 is accepted, meaning that there is a positive and significant influence between the work environment on employee performance on. Simultaneous test of motivation and work environment has a positive and significant effect on employee performance with a contribution of 48.4%, while the remaining 53% is influenced by other factors. Hypothesis testing obtained the value of Fcount> F table or (32.194> 2.770), thus Ho is rejected and H3 is accepted. This means that there is a positive and significant simultaneous influence between motivation and work environment on employee performance in Work Unit Implementation on the Jakarta Metropolitan I National Road.